Critical Analysis of Aisyah Abd Al-Rahman’s Interpretation of Al-Insan’s Pronunciation in Al-Tafsir Al-Bayani Li Al-Qur’an Al-Karim - Faqih, Sahlan Muhammad (UIN Sunan Gunung Djati Bandung, 2023)
This article targets to respond critically to Bint Al-Syathi's interpretation of the term al-insan in his commentary ‘al-Tafsir al-Bayani li al-Qur'an al-Karim’. As a support for research, this article uses qualitative techniques through records collection the usage of library studies. The method uses an analytical descriptive technique if you want to provide an authentic description of the object. as well as using a historic technique to be extra comprehensive in photographing beyond events in a measurable manner. Bint Al-Syathi has an independent approach which he applies in his interpretation based totally on literary style. whilst he explains the that means of al-insan along side its context, the consequences of its meaning will now not be separated from the regulations of the Arabic language, even though he also makes use of historical considerations based on the guidelines of ‘sabab al-nuzul’. primarily based on those considerations, Bint al-Syathi constantly consistently interprets the pronunciation of al-insan because it's far interpreted as an ism of a kind which is judged based on its generality without exception. Bint al-Syathi's view is part of the consequence in strengthening his method of Tafsir, which of path additionally has some components that can not be prevented within the process of criticism.